Efficacy of PD-1 blockade in cervical cancer is related to a CD8+FoxP3+CD25+ T-cell subset with operational effector functions despite high immune checkpoint levels. Issue 1 (12th February 2019) - Heeren, A. M.; Rotman, J.; Stam, A. G. M.; Pocorni, N.; Gassama, A. A.; Samuels, S.; Bleeker, M. C. G.; Mom, C. H.; Zijlmans, H. J. M. A. A.; Kenter, G. G.; Jordanova, E. S.; de Gruijl, T. D.
Abstract : Background: Cervical cancer (CxCa) is mainly a locally invading disease that metastasizes to loco-regional lymph node basins before involving distant organs in more advanced stages. Local immune potentiation of tumor-draining lymph nodes (TDLN) may thus protect against tumor progression. Methods: To identify therapeutic targets for local immune modulation, multi-parameter flow cytometric T-cell profiling of primary cervical tumors (PT) and TDLN ( n  = 37) was performed. The in-vitro effect of PD-1 blockade on T-cell reactivity to HPV16 E6 oncoproteins was determined in cultures of TDLN and PT single cell suspensions ( n  = 19). Also, intracellular cytokine staining (ICS) upon anti-CD3 stimulation was performed in metastatic TDLN (LN+) and PT ( n  = 7), as well as multiplexed immunofluorescence histochemistry staining ( n  = 8). Results: Our data revealed elevated rates of activated regulatory T cells (aTregs) and of central or effector memory CD8 + T cells in metastatic TDLN (LN+) as compared to tumor-free TDLN (LN-), and equally high or even higher rates of these subsets in PT. Both memory subsets co-expressed multiple immune checkpoints. PD-1 blockade significantly enhanced detectable E6-specific T-cell responses in 4/5 HPV16+ LN+ and in 1/5 HPV16+ PT. Whereas aTreg rates were higher in anti-PD-1 non-responders, in responders elevated levels of CD8 + FoxP3 + CD25 + T cells were observed, which correlated with the efficacy of PD-1 blockade ( P  = 0.018). This subset was characterized by an early effector memory phenotype with particularly high levels of co-expressed PD-1, CTLA-4, TIM-3 and LAG-3 checkpoints, but, rather than exhausted, was shown upon polyclonal activation to produce higher levels of Granzyme-B and effector cytokines as compared to its CD8 + FoxP3 − counterparts. Conclusion: These observations support local PD-(L)1 blockade to interrupt loco-regional immune suppression in CxCa and control metastatic spread to TDLN. Furthermore, our data identify CD8 + FoxP3 + CD25 + T cells as therapeutic targets, which may also serve as predictive biomarker for PD-(L)1 checkpoint blockade.